Effect of Implementing Virtual Educational Sessions on Nursing Students’ Knowledge, Attitude and Hesitancy Regarding COVID-19 Vaccination - Eman A. Fadel PhD; Eman Alshawish PhD; Rasha Hafez Ramadan El-Shaboury PhD; Dalia E. Khalil PhD; Fatma Zaghloul Mahmoud PhD; Nagwa Ibrahim El-Feshawy PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
COVID-19 vaccination is the hopeful savior to curb the pandemic. One of the most urgent public health challenges is vaccine hesitancy. Vaccine hesitancy persists despite the availability of COVID-19 vaccinations because of ignorance and unfavorable attitudes. This study evaluated the effect of virtual educational sessions on nursing students’ knowledge, attitude, and hesitancy regarding COVID-19 vaccination. A quasi-experimental 1-group pretest-posttest design was used. 350 undergraduate nursing students were recruited from each academic level using a convenience sampling technique. A self-administered structured questionnaire was used to assess nursing students’ knowledge, attitudes, and hesitancy toward COVID-19 vaccination. The Monte Carlo tests, chi-square, paired T -test, and Pearson correlation coefficient test were utilized. The mean of the total correct knowledge score and the mean of the total negative attitude score improved significantly from pre- to post-implementation of the virtual educational sessions (from 13.82 ± 5.08 to 35.59 ± 2.62 and from 36.38 ± 7.03 to 17.6 ± 5.13, respectively. Total vaccine hesitancy decreased significantly, with the proportion of doubtful and strongly hesitant students decreasing from 34.3% and 14.6% to 11.4% and 3.2%, respectively. The educational sessions had positive effects on undergraduate nursing students’ knowledge, attitude, and hesitancy regarding COVID-19 Vaccination, so Integration of the virtual educational sessions regarding COVID-19 vaccination into the curricula of educational nursing institutions is recommended.